Systematic analysis of specific and nonspecific auxin effects on endocytosis and trafficking. Issue 2 (18th March 2021) - Narasimhan, Madhumitha; Gallei, Michelle; Tan, Shutang; Johnson, Alexander; Verstraeten, Inge; Li, Lanxin; Rodriguez, Lesia; Han, Huibin; Himschoot, Ellie; Wang, Ren; Vanneste, Steffen; Sánchez-Simarro, Judit; et al.
Abstract: The phytohormone auxin and its directional transport through tissues are intensively studied. However, a mechanistic understanding of auxin-mediated feedback on endocytosis and polar distribution of PIN auxin transporters remains limited due to contradictory observations and interpretations. Here, we used state-of-the-art methods to reexamine the auxin effects on PIN endocytic trafficking. We used high auxin concentrations or longer treatments versus lower concentrations and shorter treatments of natural indole-3-acetic acid (IAA) and synthetic naphthalene acetic acid (NAA) auxins to distinguish between specific and nonspecific effects. Longer treatments of both auxins interfere with Brefeldin A-mediated intracellular PIN2 accumulation and also with general aggregation of endomembrane compartments. NAA treatment decreased the internalization of the endocytic tracer dye, FM4-64; however, NAA treatment also affected the number, distribution, and compartment identity of the early endosome/trans-Golgi network, rendering the FM4-64 endocytic assays at high NAA concentrations unreliable. To circumvent these nonspecific effects of NAA and IAA affecting the endomembrane system, we opted for alternative approaches visualizing the endocytic events directly at the plasma membrane (PM). Using total internal reflection fluorescence microscopy, we saw no significant effects of IAA or NAA treatments on the incidence and dynamics of clathrin foci, implying that these treatments do not affect the overall endocytosis rate. However, both NAA and IAA at low concentrations rapidly and specifically promoted endocytosis of photo-converted PIN2 from the PM. These analyses identify a specific effect of NAA and IAA on PIN2 endocytosis, thus, contributing to its polarity maintenance and furthermore illustrate that high auxin levels have nonspecific effects on trafficking and endomembrane compartments. Abstract : Natural and synthetic auxins affect various aspects of the endomembrane system at high concentrations, but promote clathrin-mediated endocytosis of the PIN2 auxin transporter at low concentrations.